A dual target-recycling amplification strategy for sensitive detection of microRNAs based on duplex-specific nuclease and catalytic hairpin assembly. Issue 70 (27th July 2015) - Hao, Nan; Dai, Pan-Pan; Yu, Tao; Xu, Jing-Juan; Chen, Hong-Yuan
Abstract : A dual target-recycling amplification strategy for detection of microRNAs based on duplex-specific nuclease and catalytic hairpin assembly was reported. Abstract : A dual target-recycling amplification strategy for sensitive detection of microRNAs based on duplex-specific nuclease and catalytic hairpin assembly was reported for the first time.